Molecular characterization of Newcastle disease virus strains isolated from different outbreaks in Northeast India during 2014–15. (February 2016) - Nath, Barnali; Barman, Nagendra N.; Kumar, Sachin
Abstract: Newcastle disease virus (NDV) isolates recovered from different outbreaks in chicken flocks in Assam during 2014–15 were genotypically and pathotypically characterized. Nucleotide sequence analysis of fusion (F) and hemagglutinin protein genes showed a close similarity with genotype XIII strains of NDV. Amino acid sequence of F protein showed a virulent cleavage site 112 R-R-Q-K-R-F 117 . Furthermore, pathogenicity test in one-day-old chicks and embryonated chicken eggs showed a virulent pathotype of the isolated NDV strains. The study will help us to understand the biology of circulating strains of NDV in Northeastern part of India. Highlights: Newcastle disease virus (NDV) isolates from Northeast India. Genotypic and pathotypic characterization of NDV isolates. Phylogenetic characterization of NDV isolates.